Can an educational application increase risk perception accuracy amongst patients attending a high-risk breast cancer clinic?. (April 2017) - Keohane, D.; Lehane, E.; Rutherford, E.; Livingstone, V.; Kelly, L.; Kaimkhani, S.; O'Connell, F.; Redmond, H.P.; Corrigan, M.A.
Abstract: Objectives: To design, develop and test the effect of an educational initiative to improve risk perception amongst patients attending a high-risk breast cancer clinic. This was achieved through three objectives – 1. identifying an optimal method of presenting risk data, 2. designing and building a risk application, and 3. testing the ability of the application to successfully modify patients perceived risk of cancer. Materials and methods: A mobile application was developed for this project using best practice methods for displaying risk information. Patients (n = 84) were randomly allocated into two groups – 'Control' or 'Treatment'. Both groups underwent standard risk counseling while the application was employed in the 'Treatment' group. The patients were surveyed before their session, immediately after and six weeks later. Results: Increases in accuracy were seen in both groups with larger increases demonstrated in the 'Treatment' group with 'Personal 10 Year Risk' statistically significant ('Control' group increase from 21% to 48% vs the 'Treatment' group increase from 33% to 71% - p = 0.003). Conclusion: This project demonstrated trends towards improved risk perception, however mixed logistic regression was unable to show a 30% difference between groups. Numerical literacy and understanding of risk were identified as issues amongst the general population. Overestimating risk remains high amongst attendees. Using mobile applications to convey risk information to patients is a new and evolving area with a corresponding paucity of data. We have demonstrated its potential and emphasised the importance of designing how this information is communicated to patients in order to make it understandable and meaningful.